Hardware Man-in-the-Middle Attacks on Smartphones - Mohamed Amine Khelif; Jordane Lorandel; Olivier Romain (Forensic Science Today - Peertechz Publications, 2020)
With the democratization of smartphones, law enforcement agencies are increasingly faced with the necessity of extracting data from criminal devices. Several vulnerabilities can be exploited to extract these data, but they are usually quickly fixed by a software update as soon as they are discovered by the manufacturers. We propose a new hardware/protocol based attack targeting data communication bus of a smartphone. This attack is more robust to countermeasures, and allows to have a real-time access to the data exchanged for further processing.